Diagnosis of Hirschsprung's disease in children: Preliminary evaluation of a novel endoscopic technique for rectal biopsy. Issue 6 (4th October 2018) - Nabi, Zaheer; Shava, Upender; Sekharan, Anuradha; Nageshwar Reddy, Duvvur
Abstract : Background and Aim: The diagnosis of Hirschsprung's disease (HD) relies on anorectal manometry and rectal biopsy. The role of endoscopic biopsy is uncertain for the diagnosis of HD in children. In this study, we evaluated the adequacy of biopsies procured by endoscopic mucosal resection (EMR) for the diagnosis of HD. Methods: Consecutive children with suspected HD from January 2013 to January 2018 were enrolled in the study. EMR was performed using the standard band ligation device at a distance of about 3 cm from dentate line in rectum. All samples were assessed macroscopically and microscopically. An adequate sample was defined as those measuring >3 mm and including adequate submucosa. Results: A total of 132 children underwent evaluation for constipation in the study period. Of these, 10 children (median age, 4.25 years) underwent EMR using the band ligation device for the evaluation of HD. EMR was performed with and without submucosal lifting injection in four and six children, respectively. All the samples were adequate macroscopically (>3 mm). Absence of ganglion cells was noted in six children. Of these, three children underwent full‐thickness rectal biopsy followed by surgery. Three children did not undergo surgery. Ganglion cells were identified in four children, thereby excluding the diagnosis of HD. Conclusion: Rectal biopsy using EMR with a band ligation device is feasible, safe, and provides adequate sample for the evaluation of HD in children. Abstract : Endoscopic rectal biopsy using band assisted endoscopic mucosal resection is a useful technique for evaluation of suspected Hirschsprung's disease in children.